Wireless link evaluation of a dielectric resonator nanoantenna - Malheiros-Silveira, Gilliard N. [UNESP]; Rubio-Noriega, Ruth E.; Hernandez-Figueroa, Hugo E. (SPIE, the international society for optics and photonics, 2019)
Optical antennas/nanoantennas are optical elements that have gained highlight in this decade and have potential application in several branches of photonics/plasmonics, such as, optical sensors, lasers, solid state lighting, photovoltaics, microscopy, etc. Additionally, the dipole nanoantennas have been the antennas elements mostly studied in proposals for those applications and, in special, for free-space communication based on plasmonic circuits. Here we report some advantages of dielectric resonator nanoantennas (DRNAs) as elements for coupling light to plasmonic-based circuits. Fundamental antenna parameters such as reflection coefficient, gain, efficiency, among others, are evaluated and its advantages are highlighted for nanophotonics applications. A study about an optical link for circuits based on metal-dielectric-metal-dielectric (MDMD) nanostrip waveguides operating at the central wavelength of λ0 = 1.55 μm is evaluated. We studied the coupling of near- and far-fields of a DRNA matched to an MDMD nanostrip waveguide. The results show the advantage of it as an element for optical coupling from/to free-space as well as to establish a wireless optical link for inter-chip communication.
Keywords: Nanoantennas; Optical antennas; Plasmonics; Wireless optical link